'I Did it For the Money': Incentives, Rationalizations and Health. (14th October 2014) - Gorin, Moti; Schmidt, Harald
Abstract: Incentive programs have been criticized due to concerns that extrinsic rewards can 'crowd out' intrinsic motivation, and also that such programs might exert a corrupting influence on those receiving the incentive. Jonathan Wolff has argued that while these worries are in some instances well grounded, incentives can also operate by liberating people from social pressures that stand in the way of their intrinsic motivations. We further develop Wolff's insight by articulating a framework for assessing such incentives and discussing several areas of public health where incentives may play a positive role. In so doing, we describe the limitations of Wolff's thesis as well as the opportunities it presents. Finally, we suggest that there is an additional attractive feature of incentives that has been overlooked, which is their capacity to serve as 'conversation makers'. By providing people an occasion to discuss reasons for and against various health behaviors, incentives have the potential not only to impact the health behavior of individuals but to affect cultural change at the population level.